Development of Artificial Intelligence-Based Chatbot Teaching Materials on the Material of the Human Blood Circulatory System for Grade V - Istiqomah, Khusnul; Setyaningrum, Vidya; Atmaja, Dwi Surya (Perspektif Pendidikan dan Keguruan, 2023)
This study aims to describe product development steps, quality results for the development of chatbot teaching materials, and student responses from the use of chatbot teaching materials on human circulatory system material. This research uses the Research and Development (R&D) method with a 4D model (define, design, development, dessimate). Product testing was carried out with 28 students of class V SD. The validation test was carried out by two material experts, two software experts, and two language experts. The result was that a value of 1 was obtained in the "very high" category for each validation. Therefore it was concluded that it was valid in developing chatbot teaching materials with material on the human circulatory system for class V SD. Chatbot teaching materials can be used in the process of learning activities. In the method of distributing chatbot teaching materials to fifth grade students, good response results were obtained, so that teaching materials in the form of chatbots on circulatory system material can be declared valid and efficient.